The insulinoma as a diagnostically and therapeutically challenging neoplasm - Oleksa, Paulina; Sobczyk, Mateusz; Wójcik, Piotr; Żuraw, Daria; Rogowska, Monika; Słaboń, Małgorzata (Journal of Education, Health and Sport, 2021)
Introduction and purpose An insulinoma is the most common neuroendocrine tumor of a pancreas. This tumor produces insulin, which in excess causes hypoglycemic attacks, provoked by hunger or physical effort. Delays in diagnostic processes of the insulinoma are associated with the misattribution of symptoms to cardiac, psychiatric or neurological disorders. Thus, the suitable diagnostic procedures play a significant role as they ensure quick introduction of treatment. The purpose of this work is to evaluate advances in demanding diagnostically and therapeutically insulinoma. A brief description of the state of knowledge The used method was a literature review. The basic and the most common method of treating the insulinoma is a surgery. Due to this, finding precise location of the tumor preoperatively is crucial. In the diagnostics of the insulinoma both basic CT and MRI contrast enhanced and an endoscopic ultrasound, a selective arterial calcium stimulation test and the latest molecular imaging are used. In treatment process not only traditional surgical excisions were performed, but also laparoscopic and robotic surgeries turned out to be success. Conclusions Summing up, the insulinoma is a neoplasm with a wide range of therapeutic and diagnostic solutions, thanks to the progress that has been made in recent years. Although there are many difficulties on a diagnostic path of the insulinoma, new solutions and appropriate aproach make this process easier. Nevertheless, doctor’s diagnostic vigilance is essential, because consideration in the differential diagnosis the insulinoma is an essential step and without this step any further actions can be taken.